Concentrating viable airborne pathogens using a virtual impactor with a compact water-based condensation air sampler - Vass, William B.; Nannu Shankar, Sripriya; Lednicky, John A.; Alipanah, Morteza; Stump, Braden; Keady, Patricia; Fan, Z. Hugh; Wu, Chang-Yu (Aerosol science and technology, 2024)
Pathogens can be collected from air and detected in samples by many methods. However, merely detecting pathogens does not answer whether they can spread disease. To fully assess health risks from exposure to airborne pathogens, the infectivity of those agents must be assessed. Air samplers which operate by growing particles through water vapor condensation and subsequently collecting them into a liquid medium have proven effective at conserving the viability of microorganisms. We present a study that assessed performance improvement of one such sampler, BioSpot-GEM ™ , gained by augmenting it with an upstream virtual impactor (VI) designed to concentrate particles in aerosols. We demonstrate that such an integrated unit improved the collection of live Escherichia coli by a median Concentration Factor (C F ) of 1.59 and increased the recovery of viable human coronavirus OC43 (HCoV OC43) by a median C F of 12.7 as compared to the sampler without the VI. Our results also show that OC43 can be concentrated in this way without significant loss of infectivity. We further present that the small BioSpot-GEM ™ bioaerosol sampler can collect live E. coli at an efficiency comparable to the larger BioSpot-VIVAS ™ bioaerosol sampler. Our analyses show potential benefits toward improving the collection of viable pathogens from the air using a more portable water-based condensation air sampler while also highlighting challenges associated with using a VI with concentrated bioaerosols. This work can aid further investigation of VI usage to improve the collection of pathogens from air, ultimately to better characterize health risks associated with airborne pathogen exposures. Copyright © 2024 American Association for Aerosol Research